Functional and Structural Analysis of Four Novel Mutations of CYP21A2 Gene in Italian Patients with 21-Hydroxylase Deficiency - Massimi, A.; Malaponti, M.; Federici, L.; Vinciguerra, D.; Manca Bitti, M. L.; Vottero, A.; Ghizzoni, L.; Maccarrone, M.; Cappa, M.; Bernardini, S.; Porzio, O. (Hormone and Metabolic Research, 2014)
Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder mainly caused by defects in the 21-hydroxylase gene (CYP21A2), coding for the enzyme 21-hydroxylase (21-OH). About 95% of the mutations arise from gene conversion between CYP21A2 and the inactive pseudogene CYP21A1P: only 5% are novel CYP21A2 mutations, in which functional analysis of mutant enzymes has been helpful to correlate genotype-phenotype. In the present study, we describe 3 novel point mutations (p.L122P, p.Q481X, and p.E161X) in 3 Italian patients with CAH: the fourth mutation (p.M150R) was found in the carrier state. Molecular modeling suggests a major impact on 21-hydroxylase activity, and functional analysis after expression in COS-7 cells confirms reduced enzymatic activity of the mutant enzymes. Only the p.M150R mutation affected the activity to a minor extent, associated with NC CAH. CYP21A2 genotyping and functional characterization of each disease-causing mutation has relevance both for treatment and genetic counseling to the patients.
Keywords: congenital adrenal hyperplasia (CAH); CYP21A2; 21-hydroxylase; genotype-phenotype; molecular modeling